PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK OH MY GLAM (OMG) PADA PLATFROM TIKTOK DI KALANGAN GEN Z - Aura Fauziah; Nurul Aisyah; Chodidjah (PT. Hasba Edukasi Mandiri, 2026)
The rapid growth of social media, particularly TikTok, has changed Generation Z's behavior in seeking information and purchasing cosmetic products. At the same time, Indonesia's cosmetic industry has experienced significant growth, leading to increasingly intense competition. In this context, price and promotion are important factors influencing purchasing decisions. This study aims to analyze the effect of price (X1) and promotion (X2) on the purchase decisions (Y) of Oh My Glam (OMG) cosmetic products on the TikTok platform among Generation Z. This research employed a quantitative approach using a causal associative method. The sample consisted of 100 respondents selected through purposive sampling. Data were collected through questionnaires, observations, and documentation, and analyzed using multiple linear regression. The results indicate that price and promotion partially have a positive and significant effect on purchasing decisions, as evidenced by t-count values greater than t-table values and significance levels below 0.05. Simultaneously, both variables also have a positive and significant effect on purchasing decisions. Therefore, competitive pricing and effective promotional strategies through TikTok can enhance Generation Z's purchasing decisions toward OMG cosmetic products.